GxE Interaction and Stability Analysis of Maize Genotypes for Certain Quantitative Traits - Lal, Kanhaiya; Kumar, Sarvendra; Prasad, Durga; Singh, H C; Singh, Alok Kumar; Jaiswal, Ajeet; Shrivastav, Shiv Prakash; Singh, Vishal (Journal of Cereal Research, 2024)
Stability analysis helps in understanding the adaptability of a genotype for its performance over a wide range of environments. In the present field work, 54 single cross hybrids, 21 parental lines and 2 checks were evaluated under three date of sowing to assess their stability under different environments. Analysis of variance for stability revealed significant linear genotype x environment interaction for plant height and shelling percentage indicating that the behavior of the genotypes on the basis of such characters could be predicted over the environments more precisely and accurately as the G × E interaction was the outcome of the linear function of the environmental components. Among the hybrids, L3 x T1, L7 x T2 and L9 x T3 showed non- significant S2di and regression coefficient greater than unity (bi >1) with high mean value than the population mean for grain yield per plant, thereby indicating its stability under favourable environments and suitability for maximum grain yield per plant. Hybrid, L10 x T2 showed non- significant S2di and regression coefficient regression coefficient less than unity (bi<1) with high mean value than the population mean for grain yield per plant, thereby indicating its stability under unfavorable environments and suitability for maximum grain yield per plant.